SELENYUMUN GLUTATYON PEROKSİDAZ ÜZERİNE OLAN ETKİLERİNİN ARAŞTIRILMASI - DEMİRBAŞ, İRFAN (Fırat Üniveristesi, 2004)
l.OZET Bu çalışmada selenyumun glutatyon peroksidaz (GSH-Px) üzerine olan etkileri araştırıldı. Araştırmada 200-300 g ağırlığında İÎ4 adet Wistar Albino rat kullanıldı. Ratlar iki ana gruba ayrıldı. Bunlardan 96' sı periton içi ( 6' sı kontrol, 30' una 0.1 mg/kg, 30'una 0.2 mg/kg ve diğer 30'una 0.4 mg/kg sodyum selenit intraperitonal enjekte edildi) ve 18' i ağız yoluyla (6' sı kontrol, 6' sına 0.02 u.g/g ve diğer 6'sına 0.5 ug/g sodyum selenit 6 hafta boyunca verildi) yapılan uygulamalarda kullanıldı. İntraperitonal selenyum uygulamasından önce ve sonraki 4, 24, 48, 72 ve 144. saatlerde, ağız yoluyla selenyum verilmesinden önce ve sonraki 6. haftada kan ve doku örnekleri alındı. Bütün ratlar eterle uyutuldu. Ratlann kann boşlukları açılarak a. femoralisin bifurkasyon bölgesinden kan ile karaciğer ve böbrek doku örnekleri alındı. Bütün hayvanların kan ve doku GSH-Px aktiviteleri Beutler, Paglia ve arkadaşlarının Önerdikleri spektrofotometrik yöntemle yapıldı. Protein tayininde Lowry ve arkadaşlarının metodu, hemoglobin tayininde ise siyanomethemoglobin metodu kullanıldı. Selenyumun 0.1 ve 0.2 mg/kg dozlarında intraperitonal yolla verilmesinden sonra kan GSH-Px aktivitesi 24. saatte ve 0.4 mg/kg dozunda 4. saatte en yüksek düzeye ulaştı. Daha sonra GSH-Px aktivitesi 0.1 mg/kg dozda 72. saatte 0.2 mg/kg dozda 144. saatte kontrol grubu ile aynı düzeye geldi. GSH-Px aktivitesi 0.4 mg/kg dozunda selenyum uygulamasından sonra 48. saattekontrol grubuna göre düşük bulundu, 72. ve 144. saatte kontrol grubuyla aynı düzeye ulaştı. Selenyumun intraperitonal yolla verilmesinden sonra bütün dozlarda karaciğer ve böbrek dokularında GSH-Px aktiviteleri azalarak 24. saatte en düşük düzeye indi. Daha sonraki saatlerde arttığı görüldü. Böbrek GSH-Px aktivitesi ise 0.2 ve 0.4 mg/kg dozlarında verilmesinden sonra artarak 72. saatte en yüksek düzeye ulaştığı görüldü. Selenyumsuz beslenen gruplarda karaciğer ve böbrek dokusunda GSH-Px aktivitesinde düşüş olduğu tespit edildi. 6 hafta boyunca her gün 0.02 ve 0.5 fig/g sodyum selenit verilen gruplarda karaciğer ve böbrek dokusunda GSH-Px aktivitesinde artış görüldü. Bu sonuçlara göre, GSH-Px aktivitesinin selenyum tarafından etkilendiği tespit edildi. Anahtar Kelimeler: Selenyum, glutatyon peroksidaz.

This study was carried out to determine investigation of selenium effects on glutathione peroxidase (GSH-Px). In the study, 114 Wistar Albino Rat weighing between 200-300 g were used. The rats were divided into two main groups. 96 of them in intraperitoneal aplication ( 6 of them control, 30 of them 0.1 mg/kg, 30 of them 0.2 mg/kg and the other 30 of them 0.4 mg/kg were injected at the doses of sodium selenite intraperitoneally) and 1 8 of them in orally application (6 of them as control, 6 of them as 0.02 jj.g/g and 6 of the others as 0.5 \ig/g sodium selenite were given sodium selenite for 6 weeks) were used. Before and after the intraperitionally selenium application at 4, 24, 48, 72, 144th hours blood and tissue samples were taken. Before and after selenium was given orally, the blood and tissue samples were taken in the 6 weeks. All animals were anesthezied with ether. Abdominal cavities of the rats were opened and the blood samples from the birfication region of a. Femoralis, also liver and kidney samples were taken. The blood and tissue of GSH-Px aktivity of all the animals were done with the spectrophotometrical method offered by Beutler, Paglia and his friends. In the Protein analysis the method of Lowry and his friends, while in the haemoglobin analysis, the method of siyanomethemoglobin was used. The blood GSH-Px activity started to increase and observed to reach to the maximum levels at 24th hours at the doses 0.1 and 0.2 mg/kg, 4th hours at dose 0.4 mg/kg. Then the GSH-Px activities were determined to gradually decrease to the near levels of control group at 72 and 144th hours at dose 0.1 mg/kg and 144thhour at dose 0.2 mg/kg. The blood GSH-Px activity of 0.4 mg/kg dose was found to be lower than that of control group at 72th hour. Then, the GSH-Px activityies were determined to increase the near levels of control group at 72 and 144th hours. The liver and kidney GSH-Px activities started to decrease and observed to reach to the minimum levels at 24th hour in all doses (0. 1, 0.2 and 0.4 mg/kg) of ( selenium given intraperitionally. Then, the GSH-Px activities were determined to increase and GSH-Px activity of kidney observed to reach to the maximum levels at 72th hour at doses 0.2 and 0.4 mg/kg. The liver and kidney GSH-Px activities taken from rats, fed selenium deficient diet, were determined to decrease. However, the GSH-Px activities were found to increase in rats fed 0.02 and 0.5 ug sodium selenite per g for 6 weeks. The results of the study indicate that GSH-Px activities were affected in plasma, liver and kidney by selenium. Key Words: Selenium, glutathione peroxidase. 4
Investigation of selenium effects on glutathione peroxidase
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Eczacılık ve Farmakoloji; Pharmacy and Pharmacology